TIME-RESOLVED EXCITON PHOTOLUMINESCENCE IN GaSe AND GaTe. - Taylor, R; Ryan, J (1987)
Time-resolved photoluminescence measurements of the layered semiconductors GaSe and GaTe have been made using a mode-locked dye laser and a synchronously scanning streak camera. It is shown that at low excitation densities (10**1**5-10**1**7 cm** minus **3) exciton dynamics is dominated by trapping at defects. A rate equation model is developed that describes exciton formation, recombination and trapping. At 4 K we determine free-exciton recombination times of 200 ps for GaTe and 350 ps for GaSe. Trapping times of 200 and 900 ps yield capture cross sections of 1. 2 multiplied by 10** minus **1**4 cm**2 and 3. 6 multiplied by 10** minus **1**5 cm**2 for GaTe and GaSe respectively.